The effects of small-scale convection in the shallow lithosphere of the North Atlantic - Likerman, Jeremias; Zlotnik, Sergio; Li, Chun Feng (Geophysical Journal International)
Curie point depth can be used as a proxy for plate temperatures. Data from the North Atlantic (10°-50°N) are used here to determine if the observed oscillations and patterns in Curie depths could be a subproduct of small-scale thermal instabilities arising at the bottom of the lithospheric plates. Our numerical models suggest that small-scale convection (SSC) cells could produce thermal perturbations at isotherms as low as the Curie point. These results are compatible with North Atlantic observations in terms of wavelengths (150-300 km), amplitudes (∼4 km) and orientations of the instabilities. Observed Curie-point depth oscillations before the onset (70 to 90 Myr) of SSC could also be linked to other different processes. We suggest that, in the case of the North Atlantic lithosphere, the spreading rate variation and the melt and upwelling could be intricately linked and cause a different pattern of SSC. Fil: Likerman, Jeremias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Zlotnik, Sergio. Universidad Politécnica de Catalunya; España Fil: Li, Chun Feng. Institute Of Marine Geology And Resources; China